Mechanism investigation of HS radical and CS losses from positively charged biradicals of diphenyl sulfides by APCI mass spectrometry. (August 2016) - Cao, Xiaoji; Wang, Chenlu; Mo, Weimin
Abstract : Rationale: Aryl thioethers are potentially useful precursors for constructing various biologically active sulfur‐containing heterocycles. The detailed relationship between the losses of HS radical and CS with the spin multiplicity of positively charged diphenyl sulfide biradicals derived from 3‐iodophenyl phenyl sulfides has not been obtained by tandem mass spectrometry combined with theoretical calculations. Methods: Collision‐induced dissociation mass spectrometry experiments were carried out using an ion trap mass spectrometer with APCI in positive mode. The MS/MS experiment for dibenzothiophene was performed by CI triple‐quadrupole mass spectrometry in positive ion mode. The accurate masses of fragments were obtained by reflective TOFMS with an EI source. Theoretical calculations were achieved by the density functional theory method at the B3LYP level with the 6−31+G(d, p) basis set in the Gaussian 03 package of programs. Results: In the fragmentation of positively charged diphenyl sulfide biradicals, losses of HS· and CS were observed, which were proposed to originate from spin multiplicity transformation from a triplet ground state to a singlet excited state and a phenyl radical shift in triplet ground state, respectively. Moreover, a protonated dibenzothiophene intermediate was confirmed to exist in the process of HS radical loss. A linear correlation was established between the product ion abundance from the two competitive losses and the Hammett constants (σ) of substituent groups on the benzene ring. Conclusions: The eliminations of HS· and CS in the fragmentation of positively charged diphenyl sulfide biradicals were triggered by spin multiplicity transformation from a triplet ground state to a singlet excited state and a phenyl radical shift in a triplet ground state, respectively. Based on theoretical calculations, two competitive neutral losses are thermodynamically controlled. Copyright © 2016 John Wiley & Sons, Ltd.